A review of recent progress in reducing NaCl content in meat and fish products using basic amino acids. (January 2022) - Zhang, Yawei; Guo, Xiuyun; Peng, Zengqi; Jamali, Muneer Ahmed
Abstract: Background: Due to the high NaCl contents of meat products, a reduction in their sodium levels is an ongoing focus for researchers, enterprises, and consumers. Current strategies for salt reduction are limited by their negative impact on the sensory or textural qualities of meat and fish products. Scope and approach: Basic amino acids could be salt substitutes for satisfying consumer demand and fulfilling the industrial drive to provide meat and fish products with desirable textures. In this review, we present an overview of earlier published studies on the influence of basic amino acids on the muscle protein processing properties (physicochemical, gel, and emulsion characteristics) and quality (proteolysis, lipolysis, protein oxidation, lipid oxidation, sensory, and textual properties) and the underlying mechanism. In addition, we have explored the future possibilities of using basic amino acids in meat and fish products. Key findings and conclusions: Basic amino acids are promising substitutes for NaCl in meat processing because of several advantageous properties, especially at low NaCl level. Basic amino acids in combination with chloride salts, yeast extract, and other salts have been evaluated as substitutes for NaCl. It is proposed that sensory enhancement by the addition of basic amino acids can be explored from the view of taste-taste interactions. Further studies are required to determine the mechanism underlying the positive effects of basic amino acids on muscle protein characteristics, to expand their fields of application, and to understand their functionality in terms of post-mortem metabolism. Highlights: Basic amino acids could reduce sodium in meat and fish products. Properties of basic amino acids as salt substitute are highlighted. Sensory enhancement can be explored through taste-taste interaction. Emerging applications of basic amino acids are proposed.